An Appraisal Of Maqasid Al-shari'ah Classic And Recent Literature: Systematic Analysis - Ahmad Syukran Baharuddin; Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib; Muhammad Hazim Ahmad; Ruqayyah Razak; Nurul Syahirah Saharudin; Muhammad Aiman Abdull Rahim (University of Nebraska-Lincoln, USA, 2024)
Maqāsid al-Shariʿah has been typically defined as the objectives behind the Islamic rulings or the Shariʿah higher intent. This knowledge is very important for the mujtahids and Islamic scholars not only to understand or interpret the Shariʿah legal texts, but also to deduce solutions for contemporary problems faced by Muslims. Maqāsid al-Shariʿah is traditionally divided into three levels of necessity, which are necessities (al-Ḍaruriyyāt), needs (al-Ḥajiyyāt), and luxuries (al-Taḥsiniyyāt). Extensive discussion of maqāsid al-shariʿah in Islamic jurisprudence has led to the classification of five elements of preservation, inter alia, protection of faith or religion (Hifz al-Din), protection of life (Hifz al-Nafs), protection of lineage (Hifz al-Nasl/Nasb), protection of intellect (Hifz al-‘Aql), and protection of property (Hifz al-Māl). The objective of this study is to systematically analyse the classical and recent literature related to maqāsid al-shariʿah. This qualitative study employs systematic literature review to compile the classical and recent related literature which then analysed it using content analysis method by adapting deductive and inductive reasoning. The data analysed will be deductively displayed in form of matrix table. The said table is inductively clarifying the content of the major issues in each literature. The result of the study portrays the lack of explicit discussion related to maqāsid al-shariʿah in classical literatures. The issue related to the maqāsid al-shariʿah were addressed impliedly by the classical authors as they were more focusing on the basic and fundamental issues related to Islamic jurisprudence. Meanwhile, in recent literatures, the discussion has turned to be more specific, extensive and fruitful which apply to most of the field of knowledge including science and technology. As a pioneer, this study contributes in producing data from the classical literatures to the recent academic writing which can trigger more elaborative studies on maqāsid al-shariʿah. Last but not least, it also supplies the academician extensive literatures directly and indirectly discussed and related to maqāsid al-shariʿah.